Punishment and crime: The impact of felony conviction on criminal activity - Osborne Jackson (Federal Reserve Bank of Boston, 2020)
This paper uses increases in felony larceny thresholds as a negative shock to felony conviction probability to examine the impact of punishment severity on criminal behavior. In the theft value distribution between old and new larceny thresholds ("response region"), higher thresholds cause a 2 percent increase in the average larceny value within 120 days of enactment. However, within five years of enactment, response region average larceny values and rates decline 2 percent and 13 percent, respectively, in low-wage areas. Thus, under certain market conditions, smaller expected penalties may reduce incentives and deter crime in the long run.
Keywords: K14; K42; J22; 330; felony conviction; larceny thresholds; crime; theft; labor supply